Application of geophysical prospecting methods ERT and MASW in the landslide of Daofu County, China - Zhang, Gang; Tu, Fangzhou; Tang, Yushu; Chen, Xingchang; Xie, Kuilin; Dai, Sen (Frontiers in Earth Science, 2023)
As the material source of debris flow, it has significance to accurately and effectively study the underground structure of the landslide to prevent debris flow disasters.A landslide is a complex structural system, and its underground characteristics play an important role in its stability. The early identification of fracture surfaces and unstable bodies and assessment of potential hazards is essential for prevention and protection. The research object of this paper is a landslide that occurred in Yige Village, Xianshui Town, Daofu County, which is in the western Sichuan seismic belt, an area subject to frequent earthquakes. The Daofu landslide is a typical example of a landslide directly threatening the road below and forming a debris flow channel. In this study, we combined traditional methods(drilling and field investigation)with two geophysical techniques, multichannel analysis of surface waves (MASW) and electrical resistivity tomography (ERT), to obtain knowledge about the thickness of the landslide and its internal structure. Drilling provided information on soil structure and media in the landslide area. While, the inversion results of MASW and ERT, provided rich underground layer information, the reliability of which was verified by comparison with the drilling experimental data. Our results show that the use of MASW and ERT can quickly and effectively describe the subsurface characteristics of clay slopes for risk assessment and mitigation of landslides.